Improving Reading Comprehension Skills among English Language Students with Learning Disabilities According to Some Variables - Khasawneh, Mohamad Ahmad Saleem (Soegijapranata Catholic University, 2021)
This study explored the effect of developing reading comprehension among English language students with learning disabilities using the reading speed strategy, identifying the effect of both gender, and teaching method on developing reading comprehension. To achieve the aim of the study, a test was prepared to measure reading comprehension after ensuring its validity and reliability. The study population consisted of all (200) students studying English language in the schools of the Directorate of Education for the Second Irbid Region for the second semester of the academic year 2020/2021. The study was applied to a sample of (80) male and female students, who were selected in the simple method. The participants were distributed into two experimental groups, which received the training, and another two control groups, which studied the same educational material in the traditional method. The test was applied to the study groups before starting the implementation of the study to ensure the equality of groups. The results showed clear differences in the mean scores of the experimental group students and those of the control group students, and in favor of the experimental group. The results also showed that there were no differences between the mean scores of the students' scores attributed to gender.